Evaluasi Aspek Lanskap Ramah Lansia pada Lapangan Puputan Margarana Renon, Denpasar-Bali - Darung, Jackobus Julindro; Semarajaya, Cokorda Gede Alit; Krisnandika, Anak Agung Keswari (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024, 2024)
Abstract Evaluation Of Eldery-Friendly Aspect In Puputan Margarana Field Renon. City parks are public open spaces that can be used to conduct various kinds of activities. Therefore, good city parks should be designed to be suitable to elderly people who have physical limitations. The purpose of this study is to identify the landscape criteria for elderly-friendly parks and evaluate the compatibility of the elderly-friendly aspects of the city parks according to the compiled criteria. This study uses a survey method with descriptive and quantitative analysis data collection techniques using the KPI (Key Performance Index) method. The assessment of this study are divided into 4 (four) assessment indicators, which are : location, accessibility, vegetation and facilities. The results of the study shows that vegetation is the indicator with the highest rating and accessibility is the indicator with the lowest values. Overall, the selected city parks are quite friendly to the elderly, but several aspects need to be considered to make the parks more friendly to the elderly.   Keyword: Accessibillity, Facilities Location, Vegetatio n